Recollection and Metaphysics in Plato (Revista Archai, 2019)
In recent scholarship, the doctrine of recollection has been studied to a much lesser extent than the other main themes of Plato's philosophy. Most of the modern scholars seem to consider the doctrine of recollection as a research method. They also seem to marginalize the reference to two worlds and the soul's movement between these worlds. This article intends to show that the doctrine of recollection not only is the necessary condition of possibility of our cognitive operations (not a research method), but also it is so only because of its metaphysical dimension.